Factors influencing memorable tourism experience of visitor at A’ Famosa Safari Wonderland, Malacca - Leong, Lai Wan (2019)
Memorable tourism experience is an important aspect to visitors. The study was conducted in A’ Famosa Safari Wonderland (AFSW) to explore visitors’ memorable tourism experience based on different activities. The purpose of the study was to determine the factors influencing memorable tourism experience of visitors and also explore the relationship between eight factors that influencing visitors’ memorable tourism experience and intention to revisit A’ Famosa Safari Wonderland. A total of 400 respondents participated in the questionnaire survey. The study utilised the questionnaire to determine scores of memorable tourism experience of visitor in AFSW. Results indicated that highest mean score is meaningfulness which is 3.98. The lowest mean score is adverse feeling which is 2.02. One-way ANOVA analysis showed that the visitor with lower income have significant different on novelty and knowledge; whereas student have significant different on meaningfulness. Multiple linear regression analysis showed that the novelty, local culture, refreshment and involvement influenced the intention to revisit of visitor.